If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20y + 13 = 15y + -8 Reorder the terms: 13 + 20y = 15y + -8 Reorder the terms: 13 + 20y = -8 + 15y Solving 13 + 20y = -8 + 15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15y' to each side of the equation. 13 + 20y + -15y = -8 + 15y + -15y Combine like terms: 20y + -15y = 5y 13 + 5y = -8 + 15y + -15y Combine like terms: 15y + -15y = 0 13 + 5y = -8 + 0 13 + 5y = -8 Add '-13' to each side of the equation. 13 + -13 + 5y = -8 + -13 Combine like terms: 13 + -13 = 0 0 + 5y = -8 + -13 5y = -8 + -13 Combine like terms: -8 + -13 = -21 5y = -21 Divide each side by '5'. y = -4.2 Simplifying y = -4.2
| 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= | | 2(4z-2)-2(5-3z)=4 | | 5x+5=4x+4 | | 11+2(3n-11)=1 | | 6((2n^2)+3n-35)=0 | | (3x+4)-30=0 | | t-45=-48 | | 4x+8y-3x+2y= | | 1x+2y=18 | | 12+3(z-4)=-5z+5 | | -3(x+12)=16-x | | -6(n+3)+21=-3n-6 | | -2(2x+5)= | | 1x+2y+3z=18 | | (2x+13)=-81 | | 4(2x-6)= | | 17-13=2(x-6) | | 2u^2+2v^2+4=0 | | (2x-6)=28 | | 5(3c-1)-2=12c+2 | | -6x+12=2(3x-4) | | -2v-16=-8v+40 | | 4t-4=5(t+4) | | Y=-0.3X^2+4X-1 |